2011
DOI: 10.1007/s10570-011-9592-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cellulose crystals during prehydrolysis and soda delignification of sugarcane lignocellulose

Abstract: This work investigates the evolution of cellulose crystals from sugarcane lignocellulose (bagasse and leaves) submitted to prehydrolysis (hydrothermal, dilute acid, or steam explosion) and soda delignifications. Raw and treated materials are characterized by X-ray diffraction with modeling of area-detector patterns. Three treatment effects are correlated: increase in cellulose content, quantified by strong acid hydrolysis; increase in average cellulose crystallite width, inferred from sharper 200 diffraction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
6
47
0
2
Order By: Relevance
“…The rodlike nature of these structures may also mean that further reduction of longitudinal dimensions would achieve limited additional gain in accessible surface area and in digestion yield. X-ray diffraction measurements showed that some decrystallisation of the cellulose fibrils in all three biomass species was caused initially by hydrothermal treatment, from Table 4, which has been observed in earlier studies [37]. However, no further loss of crystallinity had occurred due to wet ball-milling, and in fact, there was a moderate increase in cellulose crystallinity, similar for all three biomass species, probably as a result of water-induced recrystallisation (hornification) due to the additional drying step required for XRD measurement [38].…”
Section: Relationships Between Digestibility and Materials Propertiessupporting
confidence: 71%
“…The rodlike nature of these structures may also mean that further reduction of longitudinal dimensions would achieve limited additional gain in accessible surface area and in digestion yield. X-ray diffraction measurements showed that some decrystallisation of the cellulose fibrils in all three biomass species was caused initially by hydrothermal treatment, from Table 4, which has been observed in earlier studies [37]. However, no further loss of crystallinity had occurred due to wet ball-milling, and in fact, there was a moderate increase in cellulose crystallinity, similar for all three biomass species, probably as a result of water-induced recrystallisation (hornification) due to the additional drying step required for XRD measurement [38].…”
Section: Relationships Between Digestibility and Materials Propertiessupporting
confidence: 71%
“…It should be noted that the apparent decrease of the XRD (200) peak width could also be caused by an increase in cellulose crystalline amount [26]. The increase in crystallite thickness has been reported to be caused by aggregation of cellulose microfibrils during heat treatments [9]. It is also noteworthy that the center of the XRD (200) peak has shifted slightly (2θ = 22.1°→ 22.4°) after the 130°C treatment and has remained constant after the introduction of oxygen reagent.…”
Section: Change In Crystalline Cellulose During Oxygen Delignificationmentioning
confidence: 99%
“…The peak center for pure microcrystalline cellulose Iβ is 22.8°. Hence, this slight shift of (200) peak towards pure cellulose peak position may imply the reduction of structural distortion of cellulose, potentially due to the removal or relocation of matrix components from cellulose crystallites [9].…”
Section: Change In Crystalline Cellulose During Oxygen Delignificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This evaluation should be made together with chrystallinity (Driemeier et al, 2011) and pre-treatment used. Important conclusion of this analysis is that the method is suitable for many different lignocellulosics, without modifications.…”
Section: Fig 2 Total Extractives Amount Present In Lignocellulosic mentioning
confidence: 99%